2008
DOI: 10.1089/jwh.2007.0594
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity, Food Intake, and Cravings with Premenstrual Syndrome: A Pilot Study

Abstract: Objective-The objective of this pilot study was to evaluate possible differences in insulin sensitivity, food intake, and cravings between the follicular and luteal phases of the menstrual cycle in women with premenstrual syndrome (PMS).Methods-Subjects were screened for PMS using the Penn Daily Symptom Rating (DSR) scale. Each subject had two overnight admissions (once in each cycle phase) to the Hospital of the University of Pennsylvania. They performed 3-day diet histories prior to each hospitalization. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…In the laboratory study of Valdes and Elkind-Hirsch [29], significant differences in the insulin resistance of healthy women during the follicular and luteal phases were observed. In one other study, no significant differences in insulin resistance during the menstrual cycle phases were seen either in healthy women or in patients with PMS [11]. Widom et al [30] indicated that women who exhibited significantly higher estradiol levels in the luteal phase were observed to have significantly lower insulin resistance during this same phase of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the laboratory study of Valdes and Elkind-Hirsch [29], significant differences in the insulin resistance of healthy women during the follicular and luteal phases were observed. In one other study, no significant differences in insulin resistance during the menstrual cycle phases were seen either in healthy women or in patients with PMS [11]. Widom et al [30] indicated that women who exhibited significantly higher estradiol levels in the luteal phase were observed to have significantly lower insulin resistance during this same phase of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a power of 90% to find a significant difference regarding the preliminary study [11] ( p =0.05, 2-sided), 19 subjects were required for each study group. We planned to enroll 30 subjects per group to compensate for any refusal to provide data or nonvaluable subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Premenstrual symptoms, while varied, generally include negative changes in mood, behavior, and well-being (including body image) and increased food cravings (Michener et al 1999; Mitchell et al 1991; Trout et al 2008). Up to 90% of women experience premenstrual symptoms (Campagne and Campagne 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Larger amounts of carbohydrates and lipids in women with PMS in the luteal phase of the menstrual cycle were also observed in another (pilot) study, which evaluated possible differences in sensitivity to insulin, food consumption and food cravings in PMS women during the luteal and follicular phases of the menstrual cycle. No statistically significant difference was found in insulin sensitivity and food consumption, but in all cases the amount of macronutrients was slightly larger in the luteal phase [32].…”
Section: Discussionmentioning
confidence: 63%